Prevalence and Risk Factors of Human Herpes Virus Type 8 (HHV-8), Human Immunodeficiency Virus-1 (HIV-1), and Syphilis among Female Sex Workers in Malindi, Kenya - Nzivo, M. M.; Odari, E. O.; Kang’ethe, J. M.; Budambula, Nancy (Hindawi, 2019)
The prevalence of Human Herpes Virus type 8 (HHV-8), Human Immunodeficiency virus (HIV), and syphilis is high in Sub- Saharan Africa. Studies on HHV-8 in Kenya are few and data on its coinfection with HIV and syphilis scanty. This crosssectional study among female sex workers (FSWs) in Malindi, Kenya, aimed to determine the prevalence of HHV-8, HIV, and syphilis mono/coinfections and identify associated risk factors. A total of 268 FSWs consented and were administered a structured questionnaire and screened for antibodies against HHV-8, HIV, and syphilis following the National Guidelines. FSWs positive for HHV-8 were 67/268 (25%), HIV 44/268 (16.4%), and 6/268 (2.24%) for syphilis. Eight out of 67 (12%) tested positive for HHV- 8/HIV and 2/67 (3%) for HHV-8/syphilis coinfections. Married FSWs had higher odds of HHV-8 infection (OR 2.90, 95%, and P=0.043). Single marital status was inversely associated (OR 0.46, 95% CI 0.23-0.94, and P=0.034) with HIV infection. HIV was associated with increasing age (OR 14.79, P<0.001), inconsistent condom use (OR 2.69, P=0.004), increased duration as sex worker ≥6 (OR 3.0, P=0.002) and clients ≥4 (OR 4.0, P<0.001), intravenous drug use (OR 2.5, P=0.043), and early sex debut (P=0.049) unlike HHV-8 which was not associated with high risk sexual behavior. HHV-8/HIV coinfection was associated with increasing age (OR 11.21, P=0.027). Infection by HHV-8 was not significantly associated with HIV (OR 0.62; P=0.257) or syphilis (OR 1.52; P=0.636). There was a high likelihood of infection withHHV-8 compared to HIV (OR 8.6, P=0.014) and syphilis (OR 14.6, P<0.001). The lack of association of HHV-8 with high risk sexual behavior suggests that sexual transmission may not play a significant role in transmission of HHV-8 among FSWs in Malindi.